Peran Roh Kudus dalam Menuntun Orang Percaya kepada Seluruh Kebenaran Berdasarkan Yohanes 16:13 - Yonatan Alex Arifianto; Asih Rachmani Endang Sumiwi (Sekolah Tinggi Teologi Real Batam, 2020)
Christian faith recognizes the existence of the Holy Spirit as the divine person promised by Jesus. But not all Christians experience the involvement of the Holy Spirit in their lives. Whereas a person who is led by the Holy Spirit will experience spiritual growth, so that he lives according to God's truth and his life bears witness. This study aims to answer the question, what is the role of the Holy Spirit in the lives of believers in leading to all truth? This research is a library research using descriptive analysis method, with the Bible as the main source and support of reliable literature. The conclusion of this research is, first, the Holy Spirit makes the person he leads free from sin and intimidation from the evil one. Second, the Holy Spirit gives wisdom and understanding to know Jesus and live it at every step of the life journey. Third, the Holy Spirit leads to the whole truth of God, so that the person he guides avoids deception.